Peran Pustakawaan Dalam Peningkatan Program Literasi Di MTs At-Taufiq Bogem Jombang - Beny Sintasari; Salisnawati Salisnawati (At Tadbir: Journal of Islamic Education Management is published by the Islamic Education Management Study Programme, IAI al Urwatul Wutsqo, Jombang, East Java, Indonesia., 2023)
Librarians have a very important role in providing assistance for students to utilize and use library materials properly, correctly, and effectively, and librarians are also very influential in increasing student interest in and visits to the library. This study aims to: 1. Describe the role of librarians in developing literacy programs at MTs At-Taufiq Bogem. 2). Describe the Literacy Program's role in increasing student interest and visiting the library at MTs At-Taufiq Bogem. The method used is a qualitative method with a qualitative descriptive design and data collection techniques through observation, interviews, and documentation. Furthermore, data analysis was carried out using descriptive and qualitative analysis. The results of the research show that: 1). The role of librarians in improving literacy programs consists of: a). Librarian administrators carry out planning, organizing, and coordinating, b) Educators develop a good personality, such as in service, fostering and developing skills, increasing insight, and being able to innovate. c). Supervisors always work together to motivate colleagues, have new innovations, and always think of continuing to grow in the future